2018
DOI: 10.1002/arch.21467
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of two novel C‐type lectins from the larvae of housefly, Musca domestica L.

Abstract: Lectins and antimicrobial peptides (AMPs) are widely distributed in various insects and play crucial roles in primary host defense against pathogenic microorganisms. Two AMPs (cecropin and attacin) have been identified and characterized in the larvae of housefly. In this study, two novel C-type lectins (CTLs) were obtained from Musca domestica, while their agglutinating and antiviral properties were evaluated. Real-time PCR analysis showed that the mRNA levels of four immune genes (MdCTL1, MdCTL2, Cecropin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…Further study showed that HepCL could regulate the expression of antimicrobial proteins (Figures 6, 7). Invertebrates lack an acquired immune system, and effector molecules such as antimicrobial peptides (AMPs) play important roles in innate immunity (53). The rapid synthesis and release of active AMPs is a significant strategy in invertebrate host defenses.…”
Section: Discussionmentioning
confidence: 99%
“…Further study showed that HepCL could regulate the expression of antimicrobial proteins (Figures 6, 7). Invertebrates lack an acquired immune system, and effector molecules such as antimicrobial peptides (AMPs) play important roles in innate immunity (53). The rapid synthesis and release of active AMPs is a significant strategy in invertebrate host defenses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to binding and agglutination activities, CTLs, as PRRs, also exhibit antimicrobial activity by regulating the expression of AMPs. AMPs are generally small cationic molecules that exhibit bioactivity against bacteria, fungi and viruses (Zhou et al , ). EsLecH (APA32005) can regulate AMPs via JNK signalling to restrain bacterial proliferation (Zhu et al , ) .…”
Section: Discussionmentioning
confidence: 99%
“…Aedes aegypti mosGCTL-1 collaborates with the human CD45 homolog mosPTP-1 to enable attachment and entry of the West Nile virus (WNV) [ 21 ]. In Musca domestica L, MdCTL1 and MdCTL2 could effectively reduce the infection of Sf 9 cells by Autographa californica multicapsid nucleopolyhedrovirus (AcMNPV) and dramatically inhibit the proliferation of influenza H1 N1 virus [ 22 ]. In short, the roles of insect C-type lectins in viral infection have been increasingly investigated and reported.…”
Section: Introductionmentioning
confidence: 99%